The Contribution of Mosque-Based Sharia Cooperatives to Community Well-Being Amidst the COVID-19 Pandemic - Wartoyo Wartoyo; Nur Kholis; Ah. Ali Arifin; Nur Syam (IQTISHADIA, 2022)
Mosque-based sharia cooperatives are Islamic microfinance institutions with two unseparated financial and social missions. They have unique characteristics not found in other cooperatives and financial institutions and could become the ideal institutions for the community, especially in the COVID-19 pandemic. However, to date, researchers have neglected this phenomenon. Therefore, this study explores the contribution of mosque-based sharia cooperatives during the COVID-19 pandemic to the community’s well-being. The researchers employed participant observation and semi-structured interviews to collect the study data and then interpreted them using an inductive approach. This study showed that mosque-based sharia cooperatives had several critical contributions to community well-being during the pandemic, including cheap financing with the qardhul hasan contract, refinancing and rescheduling loan, delivering basic food packages through zakat funds and cross-subsidies, carrying out social services, and health education. The findings confirm previous research indicating that mosque-based sharia cooperatives significantly improved community livelihood. Furthermore, this study contributes to the expanded understanding that sharia cooperatives integrated with mosques augment their contributions to community well-being in the pandemic.